The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.56431/p-24wq2e
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plant Water Status, Biochemical Attributes and Seed Quality of Black Gram and Green Gram Genotypes under Drought

Abstract: Drought is one of the major abiotic stresses which adversely affect crop growth and production worldwide as water is vital for every aspect of plant growth and development. The present experiment was carried out during the growing seasons (September – December) of 2012 and 2013 to evaluate the response of black gram (Vigna mungo L.) and green gram (Vigna radiata L.) in terms of some important growth indices, biochemical traits and seed quality under drought stress. Four commonly grown genotypes - T9, KU 301(bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…However, Bangar et al (2019) suggested that the vegetative stage was more sensitive to drought because the biomasses of leaves and stems do not accumulate enough before flowering. Drought reduces leaf growth at any growth stage through the reduction of leaf area (Baroowa & Gogoi, 2015;El-Nakhlawy et al, 2018). This reinforces the importance of leaf development for yield in mung bean (Geetika et al, 2022b).…”
Section: Discussionsupporting
confidence: 55%
“…However, Bangar et al (2019) suggested that the vegetative stage was more sensitive to drought because the biomasses of leaves and stems do not accumulate enough before flowering. Drought reduces leaf growth at any growth stage through the reduction of leaf area (Baroowa & Gogoi, 2015;El-Nakhlawy et al, 2018). This reinforces the importance of leaf development for yield in mung bean (Geetika et al, 2022b).…”
Section: Discussionsupporting
confidence: 55%
“…Reduced canopy development is another major effect of drought stress with a substantial reduction in leaf area and plant height (Baroowa & Gogoi, 2015; El‐Nakhlawy et al, 2018). Reduction in canopy size is an important mechanism to moderate water use and decrease cell injury during water stress (Basu et al, 2016).…”
Section: Abiotic Stresses Impacting Mungbean At the Reproductive Stagementioning
confidence: 99%
“…The delay in the eggplant variety (‘Bonica F1’) flowering time observed in this work was caused by salinity and drought stress, which should be the efficient strategy for eggplant adaptation to the challenging habitat. Earlier findings have demonstrated that salt and drought stress can contribute to the delay of plant flowering, which has a detrimental impact on crop yield [ 9 , 27 , 28 ]. The results of the current study agree with the previous findings, which might be due to higher water usage combined with later flowering times [ 27 ].…”
Section: Discussionmentioning
confidence: 99%